Changes in and the association of retinal blood perfusion and retinal nerves in diabetic patients without retinopathy - Hao, Jianchen; Du, Jiantong; Gu, Xiaopeng; Zhang, Yadi; Yang, Liu; Zhang, Shijie (Frontiers in Endocrinology, 2023)
Objective To explore intraretinal blood flow perfusion and nerve changes, as well as the correlation between them, in diabetic patients without diabetic retinopathy (NDR). Method Eighty-six NDR patients (86 eyes) who attended the ophthalmology clinic between December 2019 and December 2021 were included. Sixty-four eyes of 64 healthy examined controls in the same period were selected as the control group. The patients underwent routine ophthalmological examination, optical coherence tomography (OCT) and OCT angiography. Results The average thickness, minimum thickness and thickness of each quadrant except for the superior temporal quadrant of the ganglion cell-inner plexiform layer (GCIPL) in the macular area of the affected eyes in the NDR group were lower than that of the tested eyes in the control group (P < 0.05). The average retinal nerve fibre layer (RNFL) thickness of the NDR group and the superior, inferior and nasal quadrants around the optic disc of the affected eyes in the NDR group were lower compared with the tested eyes in the control group (P < 0.001, P = 0.003, P = 0.001, P = 0.009). The mean vessel length density in the parafoveal and perifoveal areas in the NDR group was positively associated with the mean GCIPL thickness in the macular area (ρ = 0.265, ρ = 0.257 and P < 0.001). No blood flow perfusion parameters in the NDR group were correlated with the RNFL thickness of the corresponding quadrant around the optic disc (P > 0.05). Conclusion In diabetic patients without diabetic retinopathy, the superficial retinal vessel density in the macular area positively correlated with GCIPL thickness, and the superficial retinal vessel density around the optic disc was not correlated with RNFL thickness.